Encyclopedia of Water 2019
DOI: 10.1002/9781119300762.wsts0130
|View full text |Cite
|
Sign up to set email alerts
|

Sediment Yields and Sediment Budgets

Abstract: This article aims to provide a broad overview of the topic across spatial scales ranging from small catchments to a global perspective. The two elements of the topic (i.e. sediment yields and sediment budgets) are closely related, with the former treating the catchment or river basin essentially as a black box. The latter looks into the black box to consider the importance of sediment sources, and sediment mobilization, transport, and storage in influencing sediment yields. Attention is directed firstly to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 157 publications
0
9
0
Order By: Relevance
“…Alatorre et al (2012) demonstrated that the use of catchment sediment yield data alone is not enough to allow for a robust calibration and despite it could provide reasonable predictions of sediment yield, it could offer no insight into the spatial patterns of soil erosion. Overall, similar concerns were raised by Walling (2019) who stated that by focusing on the amount of sediment exported, values of sediment yield effectively view the catchment as a black-box and no account is taken of the processes or where the sediment originates. Thus, our grid calibration enables to identify the areas that generate most sediment.…”
Section: Model Performance and Resolution Effectsmentioning
confidence: 84%
“…Alatorre et al (2012) demonstrated that the use of catchment sediment yield data alone is not enough to allow for a robust calibration and despite it could provide reasonable predictions of sediment yield, it could offer no insight into the spatial patterns of soil erosion. Overall, similar concerns were raised by Walling (2019) who stated that by focusing on the amount of sediment exported, values of sediment yield effectively view the catchment as a black-box and no account is taken of the processes or where the sediment originates. Thus, our grid calibration enables to identify the areas that generate most sediment.…”
Section: Model Performance and Resolution Effectsmentioning
confidence: 84%
“…Up to 90% of the TP load of some Danish rivers has been reported to originate from bank erosion (Kronvang et al, 1997 ). Similarly, Walling, Webb, et al ( 2008 ) and Walling, Collins, et al ( 2008 ) reported that up to 43% of the PP flux in 12 agricultural sub‐catchments in the UK originated from channel bank or subsurface source erosion. On the basis of existing studies reported in the international literature, eroding channel banks have been estimated to account typically for between 10% (Sekely et al, 2002 ) and 40% (Howe et al, 2011 ) of the total P load in any individual river catchment, although this can be upwards of 90% (Kronvang et al, 1997 ).…”
Section: Introductionmentioning
confidence: 91%
“…Within most catchments in temperate landscapes, the erosion of agricultural topsoils is the dominant source of fine‐grained sediment, and therefore of the PP, delivered to freshwaters. However, eroding channel banks can also contribute a large proportion of riverine sediment load and therefore potentially of the total PP load (Collins et al, 1997 ; Collins et al, 2012 ; De Rose et al, 2005 ; Evans, 2019 ; Evans et al, 2003 ; Imeson et al, 1984 ; Kronvang et al, 2013 ; Laubel et al, 2003 ; Lu et al, 2015 ; Miller et al, 2014 ; Neal & Andera, 2015 ; Owens et al, 2000 ; Rode et al, 2018 ; Walling et al, 1999 ; Walling & Collins, 2005 ; Walling, Collins, et al, 2008 ; Walling, Webb, et al, 2008 ; Wilkinson et al, 2005 ; Zaimes et al, 2008a ). For example, 7%–10% of the total P load of the Blue Earth River in Minnesota, USA, originated from channel bank erosion (Sekely et al, 2002 ) compared with up to 56% of the P load in rivers in central Illinois, USA (Roseboom, 1987 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations